Nanoparticles stabilized foam fluid for hydraulic fracturing application of unconventional gas reservoirs: A review of the properties, progress and future prospects - Amit Verma; Nilanjan Pal; Narendra Kumar; Ahmed Al-Yaseri; Muhammad Ali; Keka Ojha (Petroleum Research)
Nanoparticles stabilized foam fracturing fluid is an emerging technology in the field of hydraulic fracturing for the unconventional reservoirs. Hydraulic fracturing, commonly known as fracking, is a process used to extract oil and gas from the unconventional reservoirs, such as shale formations. This study has reviewed contiguous improvement in the properties of foam fracturing fluid by the effective formulation of surfactant, polymer, and nanoparticles. Compared to conventional fracturing fluids (slick water and polymer), nanoparticles stabilized foam fracturing fluids exhibit superior proppant-carrying capabilities, ensuring better penetration into micro-fractures and enhanced contact with the reservoir matrix, reduce water usage, and minimize formation damage. Foam structures at different scales, i.e., the interface between air-water and liquid film has been discussed in depth to elaborate on the mechanisms that maintain the stability of foam film. The effects of nanoparticles for improving the foam stability and liquid drainage are deliberated to throw light on the strength and limitations of the current review work for better knowledge of foam structure. This review work is on the advancement of nanoparticles foam fluid focuses on significant analyses, problems, future scope, and applications. The various knowledge gaps and conflicting observations have been identified that give the range of our studies. The technical challenges of using foam-based fracturing fluids were also explored. Maintaining foam stability at the high pressures and temperatures experienced in unconventional reservoirs is a critical challenge. The potential for foam collapse or degradation could undermine its effectiveness in delivering proppants and stimulating fractures.